A study on the application of LIS information technology subjects in BLIS graduates' work and job opportunities - Mendoza, Adeo Cyrus R.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
The developments in technology have made great impacts in the field of Librarianship. Information today comes in a wide variety of formats with different means of storage and retrieval. That is why Librarians and Information Professionals are now obliged to educate themselves with IT in order to face the current demands of the clientele. It is in this light that this study focused on the application of LIS Information Technology subjects in the work of graduates of Bachelor of Library and Information Science.
The respondents were expected to assess which LIS 160 series subjects are most often applied in actual work. Among the topics covered by LIS 160 series subjects, the top three most useful in the work of the respondents are as follows: LIS 160: "The Internet and the World Wide Web" (84.31), LIS 160: "Information Storage and Retrieval Techniques" (78.43), and LIS 160: "Application of IT to Library and Information Science" (70.59).
On the other hand, LIS 161 got an 85.71 response and was determined by the respondents as the most useful subject among the LIS 160 series subjects. Graduates' IT positions include Programmer, Network Administrator, Web Developer, and Systems Analyst. These jobs are applicable inside and outside of the Library.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Workplace literacy -- Philippines; Information science -- Vocational guidance -- Philippines -- Quezon City; Library science -- Information technology -- Study and teaching (Higher) -- Philippines -- Quezon City; Library science -- Vocational guidance -- Philippines -- Quezon City; Library education -- Curricula -- Philippines -- Quezon City